Does pre-activating domain knowledge foster elaborated online information search strategies? Comparisons between young and old web user adults. (February 2019) - Sanchiz, M.; Amadieu, F.; Fu, W.T.; Chevalier, A.
Abstract: The present study aimed at investigating how pre-activating prior topic knowledge before browsing the web can support information search performance and strategies of young and older users. The experiment focus on analyzing to what extent prior knowledge pre-activation might cope with older users' difficulties when interacting with a search engine. 26 older (age 60 to 77) and 22 young (age 18 to 32) adults performed 6 information search problems related to health and fantastic movies. Overall, results showed that pre-activating prior topic knowledge increased the time spent evaluating the search engine results pages, fostered deeper processing of the navigational paths elaborated (and thus reduced the exploration of different navigational paths) and improved the semantic specificity of queries. Pre-activating prior knowledge helped older adults produced semantically more specific queries when they had lower prior-knowledge than young adults. Moderation analyses indicated that the pre-activation supported older adults' search performance under the condition that participants generated semantically relevant keywords during this pre-activation task. Implications of these results show that prior topic knowledge pre-activation may be a good lead to support the beneficial role of prior knowledge in older users' search behavior and performance. Recommendations for design pre-activation support tool are provided. Highlights: Investigation of the impact of prior domain knowledge pre-activation on young and older users' search behavior and performance with a search engine. Pre-activation fostered deeper processing of the websites visited and queries semantically more specific. Pre-activating prior knowledge may support older users' search performance when they generated semantically specific keywords during the pre-activation task. Prior topic knowledge pre-activation may contribute to support older users' search behavior and performance.